Biodegradation of textile effluents by basidiomycetes fungi that produce ligninolytic enzymes: a brief review - Kamida, Hélio Mitoshi; Soares, Helna C. Passinho; Santos, Irailde da Silva; Uetanabaro, Ana Paula T. (SITIENTIBUS série Ciências Biológicas, 2007)
The use of the basidiomycetes fungi has become an excellent alternative in the process of biodegradation of industrial waste. The lignocellulosic fungi have a notable potential for the degradation of these residues, especially the textile industry effluents. Fungi present an efficient enzymatic system for lignocellulosic residues degradation and mineralization being useful also in the bioremediation of xenobiotic composites. This work had the objective to make a mini-review of studies on fungi that produce ligninolytic enzymes used in the biodegradation of industrial wastewater.